Mobile Money Technology And Spending Behaviour Of Students Of The University Of Ghana - Cobla, G.M (University of Ghana, 2015)
Over centuries, various technologies have been introduced to developing nations, which have aided the growth of business and made lives of individuals more comfortable. Yet, none of these technologies have had as much influence on individual consumers in developing economies as the mobile phone technology. Students are one group of people who find the mobile phone technology useful in accessing information (given its internet adaptability features). Again, students’ access to information makes it easier for them to use the technology and its various applications. Resultantly, mobile money technology is largely used among them. To the extent that the mobile money technology facilitates access to funds at any point in time, it has the potency of influencing the spending behaviour of its users. This paper investigates how the use of the mobile money technology (a mobile phone based application) among students affects their spending behaviour. A total of 506 students from the University of Ghana were sampled for the study. Ordinary least squares (OLS) regression was used to estimate the results. Among findings from the study, active use of the mobile money service (technology) has significant influence on students’ spending behaviour. On a monthly basis, students who use mobile money spend nearly 19 Ghana Cedis more than those colleagues of theirs who do not use mobile money. Students who use both mobile money and ATMs jointly spend nearly 14 Ghana Cedis more than those their colleagues who do not use who technologies jointly. Again, behavioral factors such as health condition of students, their cognitive capabilities and social status were also found to be key influences on their spending behaviour. Per the findings from the study, it is recommended that, technological growth should not be curtailed given the numerous benefits technology accrues to society, yet, students must be cautious in their use of technology so as to maximize the positive influences (such as increases in productivity) and minimize the negative influences (such as indiscriminate spending) that using technology can impact on human behaviour. It is also recommended that, mobile money operating companies give more attention to enticing the Ghanaian populace to use the mobile money technology (service) than they give to improving access to it, as it is by this means that it can most easily financially include the unbanked. At Macroeconomic level, electronic (money) credit generated by the mobile money technology should not be overlooked by policy makers when making monetary policies as it also influences individual users’ consumption spending. Policy makers need to strategize on how to manage economic shocks that could emanate from the use of the technology.
Thesis (MPhil)
Keywords: Mobile Money; Technology; Spending Behaviour; Students; The University Of Ghana; Ghana